Hermeneutics - Gilhus, Ingvild Sælid (2016)
Portugues version of Chapter 2.11 of The Routledge Handbook of Research Methods in the Study of Religion, edited by Michael Stausberg e Steven Engler. The Tradtion is authorized by Taylor & Francis, owner of the work's copyrights.